2019
DOI: 10.9734/jabb/2018/v20i130068
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Degradation and Resistance Capabilities of Marine Bacteria Isolated from Niger Delta, Nigeria on Petroleum Pollutants and Heavy Metals

Abstract: Aims: To determine multiple degradation and resistance capabilities of marine bacteria isolated from Rivers State, Nigeria on petroleum pollutants and heavy metals. Study Design: Nine treatments and the controls designs were set up in triplicates containing              100 mL of sterile modified mineral basal medium in 250 mL conical flasks supplemented with 50, 100, 200 and 300 ppm of xylene, anthracene and pyrene each; 1 % of other petroleum pollutants and 300 ppm of heavy metals, nine marine hydrocar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…RS38 which showed impressive level of growth during screening in crude oil and other petroleum products where the organisms grew at equal optical densities of > 0.2 within 14 days of incubation. Uba et al (2018) reported that the abilities of the poly aromatic degrading marine bacterial strains to degrade different hydrocarbons including crude oil were found to vary. P. vermicola strain ANT1 had moderate/heavy growth on all the substrates while the other isolates had heavy, moderate, poor and no growth on the hydrocarbon's substrates.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…RS38 which showed impressive level of growth during screening in crude oil and other petroleum products where the organisms grew at equal optical densities of > 0.2 within 14 days of incubation. Uba et al (2018) reported that the abilities of the poly aromatic degrading marine bacterial strains to degrade different hydrocarbons including crude oil were found to vary. P. vermicola strain ANT1 had moderate/heavy growth on all the substrates while the other isolates had heavy, moderate, poor and no growth on the hydrocarbon's substrates.…”
Section: Resultsmentioning
confidence: 99%
“…The samples were sieved through a 2 mm sieve to take out big grains, debris and stones. The sieved soil was ground to pass through a 0.5 mm sieve and kept for the physico-chemical analysis (Uba et al, 2018).…”
Section: Soil Sample Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…High barium content can lead to diarrhea, vomiting, difficulties in breathing, abdominal cramps, increased or decreased blood pressure, muscle weakness and numbness around the face. Uba et al (2018) studied the bioremediation of petroleum pollutants using several strains of marine bacteria. All the nine strains of the marine bacteria were fully characterized phylogenetically and molecularly and they belong to the genera: Alcaligenes, Providencia, Brevundimonas, Serratia, Myroides, and Bacillus.…”
Section: Evaluation Of Recent Research Effortsmentioning
confidence: 99%